Why GPs need to be involved in mental health research - Shelley, B; Kessler, D; Mughal, F; Creswell, C (Royal College of General Practitioners, 2021)
The growing number of people presenting with mental health problems to general practice is a worrying trend, however, the involvement of GPs in mental health research is an area for hope. Being a practising GP and an active researcher are not as incompatible as one may think — a growing number of GPs are conducting research, and in so doing, they will be influencing clinical practice and guiding health policy.